Soil compaction of rehabilitated and secondary forests at Bintulu, Sarawak - Gandaseca, Seca; Ahmed, Osumanu Haruna; Majid, N. M. (2012)
The objectives of this study were: i) to compare and determine soil compaction in three different conditions of forest land, ii) to relate soil compaction with standing trees. This study was conducted at Bukit Nyabau Universiti Putra Malaysia Bintulu Sarawak Campus (UPMKB). The study sites are at a secondary forest, rehabilitated forests (2, 6 and 10 years old), and an open area (Nirwana Reserve Forest). Soil bulk density, total organic matter content and infiltration rate of soil were analyzed to determine soil compaction. High bulk density, low organic matter content and low infiltration rate suggest soil compaction. Nirwana Forest soil was more compact compared to plots of rehabilitated and secondary forest soils. The soil compaction levels of the rehabilitated and secondary forest were not significantly different. Soil compaction has been reduced as a result of planting trees.